Training and Human Resources Development Project : Annual Report - Dialogue McGill (2007)
The McGill Training and Human Resource Development Project contributes to other Quebec government initiatives aimed at ensuring that English-speaking people in Quebec enjoy equitable access, in their own language, to the full range of health and social services available to the general population. Its two main objectives are to ensure effective communication in English between English-speaking Quebecers and the health and social services workers who serve their needs and to increase the number of English-speaking professionals working in the Quebec health and social services system. The Project involves the implementation of four measures in partnership with stakeholders concerned by the issue of access to health and social services in the English-speaking communities. The 2008-2009 year was an extension of the Project which finished in March 2008.

Bridging the Gap Meeting - Literacy Quebec (LQ) (2007)

Immigration : A Perspective from Quebec's English-speaking Communities - Quebec Community Groups Network (QCGN) (2007)
The Quebec Community Groups Network welcomes the opportunity to participate in the public consultation around planning with respect to the desired numbers of immigrants that Quebec seeks to admit over the period 2008-2010. This important consultation also provides an opportunity to examine the challenges arising from the reception and integration of immigrants.

The Baseline Data Report 2006-2007 - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2007)
In 2002, the Community Health and Social Services Network (CHSSN) was a key Contributor to the report of the Consultative Committee for English‐speaking Minority Communities to the Federal Minister of Health.1 The Consultative Committee report proposed a five year Global Intervention Plan to support the English‐speaking communities’ efforts to improve access to health and social services in their language in Quebec. The Consultative Committee emphasized that improved access was intimately tied to the ability of English‐speaking communities to develop local networks and effective partnerships with public sector agencies. It was proposed that by maintaining and improving English‐language access to a full range of health and social services across diverse regional populations that these partnerships would help to promote better health outcomes and ensure the vitality of Quebec’s English‐speaking communities. The Committee underlined the need to pay special attention to the more isolated and demographically weak communities which face special challenges in providing health and social services in English to their respective populations.
Keywords: Official Language Minority Community (OLMC)

The Twenty-Sixth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2007)

ELAN Speech to Parliamentary Committee on CBC Review - English Language Arts Network (ELAN) (2007)

Project Report : Community Health and Social Services Network (CHSSN) : Community Radio : January 1 to March 31, 2007 - Howarth, Kelly; Kueber, Russell (Community Health and Social Services Network (CHSSN), 2007)
The findings and processes were to be documented and shared with the Lower North Shore (local radio station and regional English-speaking organization, COASTERs Association). In addition, consultation and support was to be given to both service providers to increase their capacity to better serve the English-speaking regions in the future.

Discussion Document #1 : Demographics and the Long-term Development of the English-speaking Communities of the Greater Montreal Region - Quebec Community Groups Network (QCGN); Greater Montreal Community Development Initiative (GMCDI) (2007)

Community NetLink - Community Health and Social Services Network (CHSSN) (2007)

Community NetLink - Community Health and Social Services Network (CHSSN) (2007)

Dialogue : Better Communication for Better Care - Dialogue McGill (2007)

Immigration : A perspective from Quebec's English-speaking communities : Prepared for the special National Assembly Committee on Immigration - Quebec Community Groups Network (QCGN) (2007)